First indication of the coherent unipolar diffraction radiation generated by relativistic electrons; Journal of Instrumentation; Vol. 13 : Radiation from Relativistic Electrons in Periodic Structures (RREPS-17) - Naumenko G. A. Gennadiy Andreevich (2018, 2018)
Title screen